Interstrand cross-linking implies contrasting structural consequences for DNA: insights from molecular dynamics - Bignon, Emmanuelle; Dršata, Tomáš; Morell, Christophe; Lankaš, Filip; Dumont, Elise (Nucleic acids research, 2017)
Oxidatively-generated interstrand cross-links rank among the most deleterious DNA lesions. They originate from abasic sites, whose aldehyde group can form a covalent adduct after condensation with the exocyclic amino group of purines, sometimes with remarkably high yields. We use explicit solvent molecular dynamics simulations to unravel the structures and mechanical properties of two DNA sequences containing an interstrand cross-link. Our simulations palliate the absence of experimental structural and stiffness information for such DNA lesions and provide an unprecedented insight into the DNA embedding of lesions that represent a major challenge for DNA replication, transcription and gene regulation by preventing strand separation. Our results based on quantum chemical calculations also suggest that the embedding of the ICL within the duplex can tune the reaction profile, and hence can be responsible for the high difference in yields of formation.
Keywords: molekulární struktura; molekulární modely; Algorithms; DNA; Molecular Structure; Models, Molecular; Molecular Dynamics Simulation; konformace nukleové kyseliny; Nucleic Acid Conformation; simulace molekulární dynamiky; algoritmy